Dekonstruksi Prinsip Mengajar Rabi Yudaisme Berdasarkan Matius 23:3 sebagai Upaya Menemukan Hakikat Pendidikan Kristen di Indonesia - Erman Saragih; Andar Gunawan Pasaribu; Johari Manik (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
The relationship between Christian continuity and Judaism is also a fascinating study in terms of the practice of Christian education. The implementation of Christian Education often goes too far in referring to material from the teachings of Rabbi Judaism in the process of its implementation without stating the affirmation of the nature of Christian Education itself on that reference. The purpose of this manuscript is as an anti-thesis of the Jewish rabbinic teaching pattern